Formal modelling, knowledge representation and reasoning for design and development of user-centric pervasive software: a meta-review. (1st January 2011) - Soylu, Ahmet; De Causmaecker, Patrick; Preuveneers, Davy; Berbers, Yolande; Desmet, Piet
Increasing demand for large scale and highly complex systems and applications, particularly with the emergence of pervasive computing and the impact of adaptive systems, introduces significant challenges for software development, as well as for user-machine interaction. Therefore, a perspective shift on software development and user-machine interaction is required. An amalgamation of model driven development and ontologies has been envisaged as a promising direction in recent literature. In this paper, we investigate this merged approach and conclude that a merger of both approaches, from formal modelling and knowledge representation perspective, on the one hand enables use of ontologies at run-time together with rules, prominently in terms of run-time reasoning, dynamic adaptations, software intelligibility, self-expressiveness, user involvement, and user situation awareness; and on the other hand at development time, prominently in terms of automated and incremental code generation, requirement adaptability, preservation of application knowledge, and validation and verification of structural and behavioural properties of the software. The core contribution of this paper lies in providing an elaborate and exploratory discussion of the problem and solution spaces along with a multidisciplinary meta-review and identification of complementary efforts in literature required to realise a merged approach.